ANALISIS KINERJA MEDIA SOSIAL OPD PEMERINTAH KOTA BANDUNG DALAM PENYIARAN KEBIJAKAN PUBLIK - Rahmina Puspa Aliza Ridwan; Said Bambang Nurcahya; Anisa Nursyabani (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2022)
Public Policy is an agreed rule to be issued and used to regulate people, groups, and officials. Local governments in broadcasting information have switched to using social media, in broadcasting information on work programs and public policies, the effectiveness and information conveyed quickly and correctly is used to influence people's behavior. The city of Bandung with a large population and the most active social media users, through the Regional Apparatus Organization (OPD) has used social media Instagram, Facebook, and Twitter. The performance of OPD social media in the Bandung City Government, of course, has broadcast public policies in accordance with the tupoksi of each OPD to analyze the performance of the Bandung City Government's Sisal OPD media in broadcasting public policies., the methodology used in this study is descriptive analysis, this analysis method is an analysis used by the majority of analysts, to display statistics through mathematical calculations. Its function is to find out the description of the distribution of sample or population data. So that the data will be easier to understand and more informative. The data analyzed are the number of OPD social media followers, the number of Activity/policy submissions, what are the most popular policies being discussed, how many people discuss the most popular policies, what day the policy discussion gets follower interaction, how many followers interact. From this analysis, suggestions and recommendations aimed at the Bandung City Government can be used to improve and improve the management of social media so that public policy information broadcasts can be used to influence public behavior at large.